The Effects of Geomagnetic Disturbances on Electrical Power Systems - (:unkn) unknown (My University, 2016)
Solar storms that generate coronal mass ejections are a cause for concern due to the damage that they cause in high voltage power grids. Geomagnetically induced currents can be introduced onto the grid and cause many adverse effects. The vulnerability of the bulk electric power systems to such events has increased during the past few decades because the power system transmission lines have become more interconnected and have increased in length. Real and reactive power flows, voltage fluctuations, frequency shifts, undesired relay operations, higher order harmonic currents, undesired damage to assets and failure of assets are all possible outcomes from a large geomagnetic disturbance. A 100 year solar storm could cause mass blackouts and colossal damage to any high voltage power grid, if proper monitoring and mitigation techniques are not used. This thesis presents an in-depth background on geomagnetic disturbances and how they affect the electrical power grid. The thesis will model geomagnetic disturbances on a theoretical grid using the simulation software OpenDSS. The thesis will also discuss monitoring and mitigation techniques that can be applied to the power grid to lessen the chance of failure or damage to assets, and analyze real world data collected from a Midwestern solar storm that had an effect on two power transformers equipped with online monitoring.
Keywords: Asset Protection; Geomagnetically Induced Currents; GIC; Power Transformer; Solar Weather; Transformer